2022
DOI: 10.21203/rs.3.rs-1379601/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circadian Rhythm Promotes the Biomass and Amylose Hyperaccumulation by Mixotrophic Cultivation of Marine Microalga Platymonas Helgolandica

Abstract: BackgroundMicroalgal starch can be exploitedfor bioenergy, food, and bioplastics. Production of starch by green algae has been concerned for many years. Currently commonly used methods such as nutrient stress will affect cell growth, thereby inhibiting the production efficiency andquality of starchproduction. Simpler and more efficient control strategies need to be developed.ResultWe proposed a novel regulation method to promote the growth and starch accumulation by a new isolated Chlorophyta Platymonas helgol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…We used glucose and sodium acetate as a carbon source, which were the precursors of starch biosynthesis and fatty acid accumulation in microalgae, respectively [ 14 ]. Study has shown that glucose as a carbon source could upregulate the starch biosynthesis pathway in marine microalga Platymonas helgolandica [ 42 ]. In this study, the sodium acetate limited glucose utilization and the starch accumulation in Crypthecodinium sp.…”
Section: Resultsmentioning
confidence: 99%
“…We used glucose and sodium acetate as a carbon source, which were the precursors of starch biosynthesis and fatty acid accumulation in microalgae, respectively [ 14 ]. Study has shown that glucose as a carbon source could upregulate the starch biosynthesis pathway in marine microalga Platymonas helgolandica [ 42 ]. In this study, the sodium acetate limited glucose utilization and the starch accumulation in Crypthecodinium sp.…”
Section: Resultsmentioning
confidence: 99%